Collaborative knowledge management system model in facilitating knowledge sharing among halal practitioners - Abdullah, Rusli (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Knowledge Management (KM) system is recognized as a tool for helping community of practice (CoP) such as the enforcement parties, the related producers or manufacturers, as well as the customers or users in capturing, storing, disseminating, and applying knowledge for their benefits in a collaborative environment. While, halal is an object or an action of the industry which is identified by applying Islamic knowledge in ensuring the goods as a product and the services are working based on the Islamic rules and according to sharia practice in the CoP daily life. In this context, there is a lack of the existing of Collaborative KM (CKM) as a system model of the CoP to facilitate halal practitioners as a standard mechanism to share knowledge especially that is related to promote the best practice or lesson learnt for the CoP’s purposes. Therefore, there is a need of a special mechanism in terms of CKM system (CKMS)model on how to manage halal knowledge as a system called CKMS application towards quality of services (QoS) based on its KM processes which are starting from knowledge acquisition, knowledge storage, knowledge dissemination, and knowledge application. Besides that, the system model of CKMS has been translated into a system prototype by using groupware software (i.e: Lotus Notes) which is evaluated based on its usability, accessibility, reliability, and security in supporting the CoP to work collaboratively anywhere, anytime and at any platform whether through desktop or mobile computing environment.